Types and Issues of Parables of Holy Quran - Farid Ahmad Fazly; Mohammad Kazem Hasti (RIRAI Publisher, 2022)
Stories are a prominent piece of prose literature. Stories coming from Quran are the best of the stories according to their kinds based on the sayings from Quran. They are divided into two types of long stories and partitioned stories. The first part of this article discusses these kinds of stories while the second part discusses some fundamental aspects of Muslim humans such as the story and belief, story and mission, story and worshipping and story and morality. The entire purpose of these topics is motivating the human beings towards good deeds for example, integrity, truthfulness, having visions and other deeds. In general, this article analytically explains these topics and relies on a library research as well.